The Role of Employee Engagement in Mediating the Influence of Commitment and Work Environment on the Work-Life Balance of Employees at ITB Nobel Indonesia - Nurul Ainun; Ahmad Firman; Maryadi Maryadi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2026)
This study aims to analyze the influence of work commitment and work environment on work-life balance with employee engagement as a mediating variable among employees of the Institut Teknologi dan Bisnis (ITB) Nobel Indonesia Makassar. The research is motivated by the importance of maintaining a balance between job demands and personal life in private higher education institutions, where employees often face heavy administrative workloads and academic service responsibilities. The study employs a quantitative research method with an explanatory approach. The population consists of 74 employees, all of whom were involved as respondents using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares (PLS) with the SmartPLS program. The research findings indicate that work commitment and work environment have a positive and significant effect on both work-life balance and employee engagement. Employee engagement also shows a positive effect on work-life balance and partially mediates the relationship between work commitment and work environment with work-life balance. These results highlight that employees’ work-life balance is influenced not only by internal factors such as commitment, but also by supportive work environments and the level of employee involvement in their work roles. Practically, this study recommends that ITB Nobel Indonesia strengthen employee work commitment, create a more conducive work environment, and enhance employee engagement to improve overall employee well-being and productivity.